Quercetin: a flavonoid with the potential to treat asthma - Laila Rigolin Fortunato; Claudiney de Freitas Alves; Maxelle Martins Teixeira; Alexandre Paula Rogerio (Brazilian Journal of Pharmaceutical Sciences, 2012)
Allergic asthma is a complex inflammatory disorder characterized by airway hyperresponsiveness, eosinophilic inflammation and hypersecretion of mucus. Current therapies include β2-agonists, cysteinyl leukotriene receptor 1 antagonists and corticosteroids. Although these drugs demonstrate beneficial effects, their adverse side effects limit their long-term use. Thus, the development of new compounds with similar therapeutic activities and reduced side effects is both desirable and necessary. Natural compounds are used in some current therapies, as plant-derived metabolites can relieve disease symptoms in the same manner as allopathic medicines. Quercetin is a flavonoid that is naturally found in many fruits and vegetables and has been shown to exert multiple biological effects in experimental models, including the reduction of major symptoms of asthma: bronchial hyperactivity, mucus production and airway inflammation. In this review, we discuss results from the literature that illustrate the potential of quercetin to treat asthma and its exacerbations. A asma alérgica é uma doença inflamatória complexa caracterizada por hiperresponsividade das vias aéreas, inflamação eosinofílica e hipersecreção de muco. As terapias atuais incluem β2-agonistas, antagonistas do receptor 1 de cisteinil leucotrienos e corticosteróides. Embora estes fármacos demonstrem efeitos benéficos, seus efeitos adversos limitam seus usos a longo prazo. Assim, o desenvolvimento de novos compostos com atividades terapêuticas similares e reduzido efeitos adversos é tanto desejável quanto necessário. Compostos naturais podem ser utilizados nas terapias atuais, uma vez que metabólitos derivados de plantas são capazes de aliviar os sintomas de forma comparável aos medicamentos alopáticos. A quercetina é um flavonóide que ocorre naturalmente em muitas frutas e vegetais e tem mostrado vários efeitos biológicos, principalmente em modelos experimentais, incluindo a redução dos principais fenótipos da asma: hiperreatividade brônquica, produção de muco e inflamação das vias aéreas. Nesta revisão, nós discutimos os resultados da literatura que revelam o potencial da quercetina para tratar a asma e suas exacerbações.